PENGEMBANGAN MEDIA BUKU SAKU DIGITAL UNTUK PENGENALAN WISATA DANAU TELUK SERUO DI DESA SEJARO SAKTI KABUPATEN OGAN ILIR - Syafitri, Rahmia; Shomedran; Erna Retna Safitri; Henny Helmi (STKIP Subang, 2026)
This study aims to develop an educational medium in the form of a digital pocketbook for tourism introduction for youth in Sejaro Sakti Village, Ogan Ilir Regency, which is assessed from the aspects of validity and practicality. The type of research is development using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), but only covers four stages up to implementation. Data collection was conducted using questionnaires and interviews. The development results show material expert validation of 100% (very valid), media expert 75% (valid), and language expert 92% (very valid). One-to-one trials reached 90% (very practical), while small group trials reached 98% (very practical). Thus, the product is categorized as valid and very practical for use by youth in Sejaro Sakti Village as an educational medium for introducing Teluk Seruo Lake tourism.